약물알레르기 검사의 시행과 해석: 전문가 의견서 - 양민석; 반가영; 김민혜; 임경환; 권혁수; 송우정; 정재우; 이정민; 서동인; 권재우; 김세훈; 신유섭; et al. (Allergy asthma & respiratory disease, 2017)
Diagnostic methods for drug allergy include the patient’s history, in vivo skin test, in vitro laboratory test, and provocation test. However, the history is often not reliable, procedures for in vivo and in vitro tests are not standardized, and provocation tests are sometimes harmful to patients. Generally, skin prick and intradermal tests are useful for immediate reactions; in contrast, patch test and delayed reading of both skin prick and intradermal tests are helpful for delayed reactions. A drug provocation test is the gold standard for both responses, and it is necessary to be aware of exact indications and contraindications with appropriate drugs, doses, and intervals. To date, several methods have been developed to detect culprit agents for drug hypersensitivity reactions, but they are neither completely well validated nor standardized. Based on this awareness and necessity, the Korean Academy of Asthma, Allergy and Clinical Immunology launched the Standardization Committee to review the international guidelines and the literature, and then developed the consensus report on the procedures and applications of diagnostic tests for drug allergy. KCI Citation Count: 2